Advancing neurosurgical education in the age of online learning and global knowledge sharing: impact of Cerebrovascular Q&A webinar series - Faisal, Umme Habiba; Idrissi, Yassine Alami; Chaurasia, Bipin; Takasumi, Alexis; Baldoncini, Matias; Patel, Akshal; Monteith, Stephen; McDougall, Cameron; Costa, Matias (Frontiers in Surgery, 2023)
The Seattle Science Foundation created the Cerebrovascular Q&A series as a free web-based tool to educate physicians and physicians-in-training about cerebrovascular and endovascular neurosurgery across geographical boundaries and different levels of training.Objective: This study aims to assess the educational impact and clinical implications of the Cerebrovascular Q&A webinar series, hosted by the Seattle Science Foundation.Methods: A digital anonymous, self-administered survey was sent to the live webinar participants. The survey contained questions about the socio-demographic characteristics of the participants, their perception of the content of the webinar series, and its impact on academic and clinical practice. The data collected from the Survey-Monkey platform was exported to Microsoft Excel which was used to perform all statistical analyses. The viewer metrics on Zoom and YouTube were also analyzed to understand trends observed among a diverse global cohort of participants.Result: A total of 2057 people hailing from 141 countries had registered for the Cerebrovascular Q&A series. The response rate to the questionnaire was 12.63% (n = 260).Respondents hailed from 65 countries, of which the majority were from India (13.46%, n = 35) and United States (11.15%, n = 29). Most of the participants were male (82.69%, n=215), while only 15.77% (n = 41) were female. The maximum number of participants were neurosurgery attendings (36.65%, n=92) followed by neurosurgeons undergoing fellowship training (24.70%, n=62) and students who were currently in residency training (15.54%, n=39). 75.97%(n = 196) heard of the Cerebrovascular Q&A series through the emails from Seattle Science Foundation. 21.5% (n=56) learned about the webinar series through social media. 75% of participants reported that the webinar content was advanced and comprehensive, and the selection of speakers was relevant. 63.08% (n=164) found the webinars sparked innovative research ideas. Additionally, 55% (n=143) reported changes in their clinical practice based on the acquired knowledge.The findings from this study reveal that webinar-based medical education in cerebrovascular neurosurgery is highly effective and influential. Web-based platforms and social media present a potent strategy to overcome barriers, emphasizing the need for targeted efforts to engage more women in medicine and neurosurgery recruitment.